Bioethics an psychiatric dissability: clinical an juridical apects - Rueda Castro, Laura; Sotomayor Saavedra, María Angélica (Acta Bioethica, 2003)
This monography seeks to establish an interdisciplinary link between bioethics and the clinical and juridical aspects that connect with attention, protection and rehabilitation of persons with psychiatric illness. The analysis is centered those adults, on deprived of reasoning because of a psycopathologic process, entitled to civil rights, but with dificulties to exercise them due to their illness.